2018
DOI: 10.1089/acm.2017.0203
|View full text |Cite
|
Sign up to set email alerts
|

Cost Savings from Reducing Pain Through the Delivery of Integrative Medicine Program to Hospitalized Patients

Abstract: For patients receiving IM therapies, pain was significantly reduced and costs were lowered by about 4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 49 publications
2
46
0
1
Order By: Relevance
“…25 This level of change is comparable to the 2-point decrease observed in the prior evaluations of pain change after IM in oncologic, 20 cardiovascular, 21 orthopedic, 22 and hospital-wide patient populations. 19 Most importantly, for the first time in the series of the research evaluations, [15][16][17][19][20][21][22][23] the authors were able to explore the role of pain medications at the time of the IM delivery. The authors found that patients' pain medication status did not have a significant impact on their pain change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 This level of change is comparable to the 2-point decrease observed in the prior evaluations of pain change after IM in oncologic, 20 cardiovascular, 21 orthopedic, 22 and hospital-wide patient populations. 19 Most importantly, for the first time in the series of the research evaluations, [15][16][17][19][20][21][22][23] the authors were able to explore the role of pain medications at the time of the IM delivery. The authors found that patients' pain medication status did not have a significant impact on their pain change.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the authors published a study including 2,370 inpatient admissions, in which the authors again observed a 2-point decrease in pain while documenting cost savings of $898 per admission when pain was reduced by IM. 23 However, one challenge in the prior work of the authors is that due to sample size limitations, they have been unable to compare post-IM with pre-IM pain changes across clinical populations (e.g., oncology vs. orthopedic). It is reasonable to consider that the effects of IM could vary by clinical population, and if true, this variation could inform the implementation of IM services across the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The promise of IH is particularly salient in the new conventional medicine guidelines that recommend IH to address chronic pain and the devastation left in the wake of the overlapping obesity and opioid crises. 1 IH creates a viable pathway to moderate chronic pain and disease 2–4 and may also reduce cost. 5,6 Despite these promises, however, the dearth of implementation research on IH and the lack of an effective and viable clinical model challenge the sustainability of IH.…”
Section: Need For Sustainable Integrative Health Delivery Modelsmentioning
confidence: 99%
“…The results were that although patients who received integrative medicine incurred slightly higher costs than those who underwent only western medicine but that they also had a reduced all-risk mortality at both three and 12 months after discharge, which may have prevented additional costs from future admissions. Similarly, another retrospective study in Texas showed that patients who received integrative medicine were more likely to have reduced pain that resulted in an approximately 4% decrease in hospital costs [ 2 ]. These findings have implications for care providers and stakeholders, as research has shown that integrative medicine likely improves patient care and outcomes while ultimately reducing hospital costs.…”
Section: Introductionmentioning
confidence: 99%